Complex Vertebral Malformation: a Recessive Disorder in Holstein Friesian Cattle - a Review - Ashwani Sharma; Vijay Kumar; Mahdi Mahdipour; P.P. Dubey; Avtar Singh; Jyoti Joshi; Priyanka Banerjee; B.K. Joshi (Journal of Livestock Biodiversity, 2025)
The present review is a concise summary of findings on one of the most important recessive hereditary disorders, the Complex Vertebral Malformation (CVM) in cattle. It is a disease of Holstein calves characterized by complex anomalies of the vertebral column and limbs in aborted fetuses and in prematurely born, stillborn and neonates. The recessive homozygous form is lethal and since carrier animals have viability, CVM frequency increases by use of carrier bulls in Artificial insemination (AI). The gene SLC35A3 has been identified as the culprit and a point mutation was eventually identified within the alleles encoding bovine SLC35A3 in a Holstein calf affected with CVM. This mutation causes valine to phenylalanine substitution at the amino acid level. PCR-PIRA, PCR-SSCP. AS-PCR and Tetra-primer ARMS-PCR are certain PCR based techniques which could be used to screen CVM in cattle. The use of these molecular technologies promises quick detection of carriers, enables their culling and consequently controls and prevents the spread of CVM in the population.